2014
DOI: 10.1177/1010539514558332
|View full text |Cite
|
Sign up to set email alerts
|

Financial Risks From Ill Health in Myanmar

Abstract: The government of Myanmar, with support from international donors, plans to address household financial risks from ill health and expand coverage. But evidence to design policy is limited. WHS (World Health Survey) data for 6045 households were used to investigate the association of out-of-pocket (OOP) health spending, catastrophic expenditures, and household borrowing and asset sales associated with illness with key socioeconomic and demographic correlates in Myanmar. Households with elderly and young childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 18 publications
4
16
0
Order By: Relevance
“…On financial protection, for instance, our review suggests that for chronically ill, older adults and individuals with disabilities, formal insurance schemes do not guarantee protection from CHE, despite greater needs for health services [50, 81]. Our findings extend those of others, confirming that households with older adults, young children or chronically ill borrow money or sell assets to finance illness, underlining the bilateral link between health and poverty [43, 103]. Looking at a wider spectrum of health financing arrangements, a Nigerian study found that households with older adults participating in informal health financing arrangements (other than health insurance schemes) were less likely to incur CHE than those with formal schemes [104].…”
Section: Discussionsupporting
confidence: 56%
“…On financial protection, for instance, our review suggests that for chronically ill, older adults and individuals with disabilities, formal insurance schemes do not guarantee protection from CHE, despite greater needs for health services [50, 81]. Our findings extend those of others, confirming that households with older adults, young children or chronically ill borrow money or sell assets to finance illness, underlining the bilateral link between health and poverty [43, 103]. Looking at a wider spectrum of health financing arrangements, a Nigerian study found that households with older adults participating in informal health financing arrangements (other than health insurance schemes) were less likely to incur CHE than those with formal schemes [104].…”
Section: Discussionsupporting
confidence: 56%
“…The presence of an elderly person in the household was found to be significant as a risk factor for CHE in all 19 papers that evaluated this variable in their analyses (15–17, 19, 21, 22, 2528, 3234, 36, 39, 4144).…”
Section: Resultsmentioning
confidence: 99%
“…9 Malaysia and Sri Lanka have traditionally relied on public sector financing and delivery, whereas India and Myanmar rely substantially on the private sector. [10][11][12] And in contrast to the high-income countries in the region, the middle-and low-income countries rely primarily on households for long-term care and often have inadequate social protection systems. 13 Overall NCD prevalence and mortality continue to increase in the region.…”
Section: Introductionmentioning
confidence: 99%